Prospective In Vitro Comparison of Kerasave and Optisol-GS Corneal Storage Solutions. Issue 5 (12th May 2023) - Tran, Khoa D.; Ellison, Mark; Straiko, Megan M. W.; Giurgola, Laura; Gatto, Claudio; Galloway, Joshua D.; Ragazzi, Eugenio; D'Amato Tothova, Jana
Abstract : Purpose: The aim of this study was to compare the performance of Kerasave and Optisol-GS for hypothermic corneal storage for 14 days. Methods: This study was a prospective laboratory investigation. Mate corneas were recovered into Kerasave or Optisol-GS (27 pairs) and stored at 2°C to 8°C for 14 days. Corneas were evaluated by trained eye bank technicians, and study parameters were compared between the initial and final evaluations. Endothelial cell density (ECD), hexagonality (HEX), and coefficient of variation (CV) were evaluated by specular microscopy, and central corneal thickness (CCT) was examined by optical coherence tomography after 1, 3, 7, and 14 days of storage. Corneal transparency was scored using slit lamp examination at days 1 and 14. Results: Average ECD, HEX, and CV for the Kerasave (2653 ± 303 cells/mm 2, 57 ± 4%, and 36 ± 3%) and Optisol-GS (2623 ± 306 cells/mm 2, 57 ± 5%, and 36 ± 4%) groups were not significantly different at day 1. There was also no difference at any other study time points (all P > 0.05). ECD did not significantly change from day 1 to day 14 in either group ( P > 0.05), but a statistically significant change in HEX and CV was observed between day 1 and day 14 in both groups ( P < 0.01). Average CCT measured at day 1 for corneas stored in Kerasave was 622 ± 49 μm and those stored in Optisol-GS was 580 ± 35 μm ( P < 0.01). The difference in CCT measurements was not significantly different at day 14 (Kerasave: 674 ± 46 μm vs. Optisol-GS: 647 ± 58 μm, P > 0.05). Corneal transparency was not significantly different between the 2 groups at day 1 or day 14. Conclusions: The corneal quality and clinically relevant parameters including ECD, endothelial morphometry, and corneal transparency were not different in corneas stored in Kerasave or Optisol-GS for 14 days. The initial difference in CCT between the 2 groups decreased at day 14. These results demonstrated that Kerasave corneal storage solution preserves the corneal endothelium similarly to Optisol-GS.